An Investigation On The Treatment Effects On Adolescents Suffering From Depression And Anxiety - Tian Li; Emad Mohamed Nafie Abdelwahab; Suriyakala (Revista Electronica de Veterinaria, 2024)
With an emphasis on current research and evidence-based methods, this study examines the effectiveness of several treatment approaches for depressed and anxious adolescents. Problems with mental health, such as anxiety and depression, are common among teenagers and have a major influence on their emotional, social, and academic lives. Medication, lifestyle modifications, cognitive-behavioral therapy (CBT), interpersonal therapy (IPT), and other contemporary therapeutic techniques are reviewed in the research. The negative thinking patterns and behaviours linked to depression and anxiety may be effectively addressed with cognitive behavioural therapy (CBT), a goal-oriented, organised treatment. IPT has also shown promising results, especially in the management of depressive symptoms; it focuses on enhancing interpersonal interactions. For teens whose symptoms are very severe or long-lasting, pharmaceutical options such selective serotonin reuptake inhibitors (SSRIs) are examined. Medication may alleviate symptoms significantly, but it’s important to watch out for adverse effects and tailor dosage to each patient. For patients with moderate to severe illnesses, the combination of medicine and psychotherapy may greatly improve treatment results. By fostering accepting communities and decreasing stigma, school-based treatments and peer support programmes amplify the positive effects of therapy. Adolescents suffering from anxiety and depression may find relief via a combination of medicine and therapy, but they can also benefit from making positive adjustments to their lifestyle and reaching out to friends and family for support. To provide complete care for teenagers dealing with these difficult mental health disorders, future studies should keep assessing and improving these treatments to make them more effective and easier to obtain.